2005
DOI: 10.1111/j.1471-0528.2005.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Why are women still aborting outside designated facilities in metropolitan South Africa?

Abstract: Objective  To explore why South African women still abort outside designated services where there is substantial legal service provision. Design  Descriptive study. Setting  Three hospitals in Gauteng Province in South Africa. Sample  Forty‐six women attending hospital with incomplete abortion who had abortions induced outside of designated facilities. Methods  An interviewer‐administered questionnaire with open and closed questions was completed. Induction status was determined from answers to a set of closed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 8 publications
(13 reference statements)
3
116
0
3
Order By: Relevance
“…41 Another study noted that women even in metropolitan areas still self-medicated and sought traditional healers, mainly because of little information about abortion rights and perceived poor quality of designated facilities. 42 Coverage of antenatal care is very high, with 94% of women attending at least one antenatal visit. However, the timing, number, and content of these visits are not optimum for all women.…”
Section: Coverage and Quality Of Carementioning
confidence: 99%
“…41 Another study noted that women even in metropolitan areas still self-medicated and sought traditional healers, mainly because of little information about abortion rights and perceived poor quality of designated facilities. 42 Coverage of antenatal care is very high, with 94% of women attending at least one antenatal visit. However, the timing, number, and content of these visits are not optimum for all women.…”
Section: Coverage and Quality Of Carementioning
confidence: 99%
“…In South Africa, studies conducted since the implementation of CTOPA have reported on the progress made in providing TOP services, notably the increase in the number of designated facilities and staff capacity-building, as well as the ongoing challenges of negative provider attitudes [9,25,26]. However, there has been insufficient scholarly focus on the psychosocial issues faced by health care providers of abortion services [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, their reasons may also include expectation of a better quality of care in the private system, absence of bureaucratic hurdles and conscientious objectors, lack of awareness of the new law and privacy concerns. 5,15,21 Studies of clandestine services pre-legalization generally focus on issues related to access and women's perspectives. 5,13,[19][20][21] More recently, much attention has been paid to evaluate Mexico City's public facilities, where efforts have been successfully focused on improving quality of care, methods used and providers' attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…14 Experience from South Africa, where abortion was legalized in the 1990s and introduced in public sector abortion services, suggests that women may avoid public services for fear of staff attitudes, ignorance about the law, lack of information on where to access services, and fear of breaches in confidentiality. 15 Furthermore, adolescents may seek private abortion services hoping to avoid burdensome requirements, e.g. parental consent, in public facilities.…”
mentioning
confidence: 99%